2020
DOI: 10.1016/j.joei.2020.04.005
|View full text |Cite
|
Sign up to set email alerts
|

Improved model for the analysis of the Heat Release Rate (HRR) in Compression Ignition (CI) engines

Abstract: The accuracy of the Heat Release Rate (HRR) model of Internal Combustion Engines (ICEs) is highly depended on the ratio of specific heats, gamma ( ). Previous models were largely expressed as functions of temperature only. The effects of the excess air ratio ( ) and the Exhaust Gas Recirculation (EGR) rate on were neglected in most of the existing functions. Furthermore, previous HRR models were developed for stoichiometric or nearstoichiometric air -fuel mixtures in an engine condition. However, Compression I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
15
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(17 citation statements)
references
References 9 publications
1
15
0
Order By: Relevance
“…Therefore, it can be concluded that has a significant effect on when alternative fuels are used in CI engines. Olanrewaju, F.O., et al, [2] also showed that had a significant effect on when the engine was run on off-road diesel.…”
Section: Comparison Of the Modified Function And Functions From Litermentioning
confidence: 95%
See 4 more Smart Citations
“…Therefore, it can be concluded that has a significant effect on when alternative fuels are used in CI engines. Olanrewaju, F.O., et al, [2] also showed that had a significant effect on when the engine was run on off-road diesel.…”
Section: Comparison Of the Modified Function And Functions From Litermentioning
confidence: 95%
“…In this work, the modified function, ( , ) and the Leeds HRR model developed by Olanrewaju, F.O., et al, [2] were used to investigate the combustion behaviour of standard diesel (ULSD), GTL diesel, and (HVO) diesel. At low and medium loads, the effect of EGR rate on the HRR of a CI engine was found to be insignificant [2]. Therefore, EGR rate was not considered in this work.…”
Section: Previous Hrr Models Of Icesmentioning
confidence: 99%
See 3 more Smart Citations